Methodological instructions for practical work "Equipment placement for flow production workplaces" from the discipline "Fundamentals of engineering training" - Semenov, Yevhenii Oleksandrovych; Yevtushenko, Nataliіa Serhiivna; Tverdokhliebova, Natalia Yevheniivna (National Technical University "Kharkiv Polytechnic Institute", 2025)
A characteristic feature of mass production is the production of the same type of products of limited range in large quantities for more or less a long time. Large volumes of production and rather high stability of a design of a product do careful advantage of careful development of technological processes. Operations of technological processes are differentiated into individual transitions, labor methods and are performed on special high-efficiency equipment with the help of appropriate equipment. Jobs are narrowly specialized by assigning a limited number of detail operations to each of them. Under such conditions, the most efficient form of production is the organization of synchronized, fairly stable over time production production and production lines. Flow production is a highly efficient method of organizing the production process. Under the conditions of the flow, the production process is carried out in maximum accordance with the principles of its rational organization. Improving the operation of production lines can take place in the following areas: improving working conditions in the workplace; stream synchronization; reduction of equipment downtime; streamlining workplace flow; timely supply of raw materials; conducting multi-machine service and combining professions.
Keywords: methodological instructions; flow production; technological process; economic efficiency; equipment placement